We've had a hundred years of psychotherapy : and the world's getting worse - Hillman, James (New York, NY Harper Collins, 1992)
"This furious, trenchant, and audacious series of interrelated dialogues and letters takes a searing look at not only the legacy of psychotherapy, but also practically every aspect of contemporary living--from sexuality to politics, media, the environment, and life in the city. James Hillman--controversial renegade Jungian psychologist, the man Robert Bly has called "the most lively and original psychologist we've had in America since William James"--Joins with Michael Ventura--cutting-edge columnist for the L.A. Weekly--to shatter many of our current beliefs about our lives, the psyche, and society. Unrestrained, freewheeling, and brilliant, these two intellectual wild men take chances, break rules, and run red lights to strike at the very core of our shibboleths and perceptions."-
D., 4/01
Keywords: Psychotherapy--Philosophy; Psychotherapy--Social aspects--United States; Civilizations, Modern--20th Century--Psychological aspects; Psychanalysts--United States--Interviews; Hillman, James--Interviews